Prognostic Accuracy of Three COPD Classification Systems in Relation to Long-Term Mortality of COPD Patients: A Prospective Multicenter Study - Plutinsky, Marek; Brat, Kristian; Svoboda, Michal; Zatloukal, Jaromir; Popelkova, Patrice; Koblizek, Vladimir (Lung, 2019)
Recent research showed group B patients express higher mortality compared to group C patients when GOLD A-D grouping is used. We aimed to compare the prognostic accuracy of three GOLD classification systems, I-IV ("pre-2011"), A-D ("2011-2016") and A-D ("2017-present") in relation to mortality, exacerbation risk, quality of life (QoL) assessment and specific treatments use in a real-life COPD cohort. We used the data of 720 patients from the Czech Multicenter Research Database of COPD. Four-year mortality and time-to-exacerbation using the GOLD "pre-2011", "2011-2016" and "2017-present" classification schemes were assessed. Moreover, distribution of specific treatments use and QoL measures were analyzed. The GOLD I-IV classification system showed gradual increase in 4-year mortality across the stages (GOLD II 18.8%, III 28.5%, IV 38.7%) (p = 0.001). Using the A-D "2011-2016" classification scheme, group C patients had lower mortality (16.7%) than group B (18.7%) (p = 0.009). The A-D "2017-present" classification showed higher mortality in group B (25.5%) compared to group C (20%) (p = 0.05). For additional outcomes, the GOLD I-IV scheme showed highest match between the calculated 4-year exacerbation risk and QoL measures and GOLD stage/grouping. In terms of specific treatment distributions, various patterns for each GOLD classification system were observed with best match of GOLD "2017-present" system to the layout of GOLD groups and categories. We conclude the GOLD I-IV classification system had the highest accuracy related to mortality, QoL measures and exacerbation risk prediction, while the A-D "2017-present" scheme was most accurate within severity of symptoms prediction reflected also by more frequent specific treatments use.
Keywords: zdravotní stav; Humans; lidé středního věku; Disease Progression; Quality of Life; Predictive Value of Tests; Female; rizikové faktory; Aged; databáze faktografické; senioři; lidé; metody pro podporu rozhodování; kvalita života; časové faktory; Databases, Factual; ženské pohlaví; Decision Support Techniques; stupeň závažnosti nemoci; Health Status; Male; prediktivní hodnota testů; Middle Aged; prognóza; Czech Republic; chronická obstrukční plicní nemoc; Severity of Illness Index; Pulmonary Disease, Chronic Obstructive; progrese nemoci; Risk Assessment; Česká republika; mužské pohlaví; prospektivní studie; Time Factors; hodnocení rizik; Prognosis; Risk Factors; Prospective Studies